Penggelapan Dana nasabah sebagai bentuk Tindak Pidana Korupsi di Indonesia - Salmon, Harly Clifford Jonas; Baljanan, Gilbert Marc (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2024)
Introduction: Embezzlement of customer funds is a form of criminal act of corruption that harms many parties, including customers who lose their money, financial institutions whose reputation is damaged, and the public who have lost confidence in the financial system. Effective prevention and law enforcement efforts are needed to eradicate this practice.Purposes of the Research:  This study aims to describe and analyze the phenomenon of embezzlement of customer funds as a form of corruption in Indonesia. Embezzlement of customer funds is a crime that harms society and affects trust in financial institutions.Methods of the Research: The research method used is literature study which involves analysis of literature, reports, court cases, and laws related to corruption and finance in Indonesia. The data collected is analyzed qualitatively to provide an in-depth understanding of embezzlement of customer funds.Results of the Research: The research results show that embezzlement of customer funds occurs through various fraudulent schemes carried out by parties who have access to customer funds, such as bank employees, investment managers, or stockbrokers. These actions often involve the use of illegally obtained customer information or abuse of authority. Several factors influence the embezzlement of customer funds in Indonesia, including weak internal and external control systems, low integrity of individuals involved in the financial industry, and lack of adequate policies and regulations. Therefore, improvements are needed in financial governance, increased supervision, employee training, and strict law enforcement to prevent and take action against perpetrators of embezzlement of customer funds. The conclusion of this study is that embezzlement of customer funds is a criminal act of corruption that needs serious attention from the government, financial institutions and the public. With the right steps, such as strengthening regulations and increasing awareness of the risk of embezzlement of funds, it is expected to reduce incidents of embezzlement of customer funds and maintain public confidence in the financial system in Indonesia